PKM DENGAN TIM PENGEMBANGAN DESA WISATA DALAM PERENCANAAN MASTERPLAN INFRASTRUKTUR EKOWISATA DI DESA BESANG KAWAN, KELURAHAN SEMARAPURA KAJA - I Nengah Sinarta; Kadek Candrayana; Agus Kurniawan (Jurnal Abdi Daya, 2021)
Tourism plays a role in accelerating the process of economic transformation in rural areas. Village communities who initially worked as farmers were gradually able to learn to develop services to support tourism in a village. The momentum of tradition, culture and environmental exoticism can be packaged as village tourism products attractive to visitors from outside the region. Efforts to increase the number of tourist villages as an effort to move the village economy are also carried out in several villages in Bali Province. One of the village plans that will be developed as an ecotourism-based village is Besang Kawan Village which is included in the administrative area of ​​Semarapura Kaja Village. The problems faced by Partners in this case the village development team in Semarapura Kaja Village are the lack of tourism supporting infrastructure and the not yet maximized potential of Besang Kaja Village as an ecotourism village. Based on the initial survey and discussions conducted with the leaders and community of Besang Kawan Village, it is known that the village has potential in the form of religious tourism objects (Tirta Celempung Temple) and landscapes in the form of rice fields. Based on the documentation of the survey results above, information is obtained that currently, in Besang Kawan Village, there is tourism potential, and the existing infrastructure is still relatively minimal. As an initial step in the development of Besang Kawan Village as a tourist village, a jogging track is proposed that crosses the potentials of Besang Kawan Village. This jogging track will cross residential areas and rice fields. The length of the jogging track is 1878m. The design of this jogging track is paving block pavement which enhances the aesthetics of the track. At a distance of every 300m will be equipped with a rest area so that visitors can rest.